NFT-troughs for protected vegetable production in the tropics - E. S., Lim (1989)
Seasonal heavy rainfall conditions limit the production of vegetables resulting in short-supply and high prices. Covered structures used to provide protection from the adverse weather conditions during the off-season restrict the preparation of land for cultivation. A minimum or no tillage cultivaion system is desirable for vegetable crops grown under such protective covers. The use of soilless cultivation method of crop production can eliminate the need for land preparation. A soilless cultivation method, the nutrient film technique (NFT) was used for the protected crop production studies. It was found necessary to insulate the NFT system from heat build-up under local hot tropical conditions. The NFT-trough system was developed which effectively reduced heat build-up and suscessfully produced various types of vegetables. The NFT-trough system was found to be of low costs, versatile, easy to use and maintain and allowed immediate replanting of crops thereby increasing productivity in comparison with conventional cropping.